Recent Advances in Legume Crop Protection (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
The legume family is economically important and is one of the most important sources of starch, protein, oil, and vegetables for human food around the world, playing an irreplaceable role in guaranteeing human food security. The pulses are an important component of the response of the Food and Agriculture Organization of the United Nations (FAO) in emergencies. However, the frequent occurrence of diseases, pests, and weeds restrict the high and stable yield of legume crops. Major diseases of legumes include root rots, bacterial blights, and mosaic diseases. In addition, damage caused by malignant weeds, nematodes, and sap-sucking/-chewing insects is also included as a constraint on legume production. This Special Issue is focused on 13 selected topics (12 articles and 1 editorial) from different universities and research institutes. The research fields covered include mechanisms of resistance to pests and diseases, identification and monitoring of diseases, alternative control strategies, weed management, and drone-mounted multispectral imaging technology. Current problems in the prevention and control of legume crop diseases, pests, and weeds are discussed with a view to providing subsequent research and applications of key pest- and disease-monitoring and control technologies with reference points.